The Role of Diet in Psoriasis Management: A Focus on Mediterranean, Ketogenic, and Plant-Based Dietary Approaches: Review - Zukierski , Krystian; Jarych, Weronika; Michalak, Katarzyna; Mazur, Michał (Quality in Sport, 2025)
Introduction and aim: Psoriasis is a chronic immune-mediated skin disease that is increasingly recognized as a systemic inflammatory condition linked to various comorbidities, including metabolic syndrome and cardiovascular disease. Lifestyle factors, particularly diet, are receiving growing attention for their potential to influence disease activity and treatment outcomes. This review explores current evidence on the role of nutrition in the clinical management of psoriasis, with a particular focus on dietary patterns such as the Mediterranean, Ketogenic, and Plant-Based diets, and their potential to improve both skin symptoms and overall systemic health. Methods and materials: This literature review draws upon sources accessed through the PubMed and Google Scholar databases, targeting publications from the last 15 years (2010–2025). The objective was to compile a wide range of scholarly works exploring the impact of dietary patterns on the management of psoriasis, with particular attention to Mediterranean, ketogenic, and plant-based diets. Search queries included terms such as “psoriasis,” “nutrition,” “Mediterranean diet,” “ketogenic diet,” and “plant-based diet.” The studies were selected based on their scientific credibility, relevance to the topic, and methodological integrity, ensuring that only high-quality and pertinent research was included in the final analysis. Results and conclusion: Diet may serve as an important adjunct to pharmacological treatment of psoriasis, influencing both the course of the disease and associated metabolic disorders. Anti-inflammatory dietary patterns, such as the Mediterranean, ketogenic, and plant-based diets, show promising therapeutic potential. Personalized nutritional recommendations and interdisciplinary care are essential for the effective and safe implementation of dietary interventions in clinical practice.